EFFECT OF OXYGEN ION IMPLANTATION ON THE THERMOELECTRIC PROPERTIES OF FILMS n-PBTe - Kokanbaev I. M. (Galaxy International Interdisciplinary Research Journal, 2022)
Ion implantation of oxygen leads to a decrease in the electrical conductivity of ()films. Reduction of electrical conductivity and Hall concentration of ectrons () of implanted films during annealing in vacuum. With thermal annealing in air, the intensity of the decrease in electrical conductivity in both implanted and non-implanted oxygen films is much higher than when annealing implanted samples in a vacuumσn_H ո-РƅTe¬¬¬